An Efficient Method for Similarity Measure in Independent PCA based Classification - Kekre, Dr. H. B.; K. Sarode, Dr. Tanuja; K. Save, Jagruti (INTERNATIONAL JOURNAL OF COMPUTERS & TECHNOLOGY, 2013)
The paper presents a new approach of finding nearest neighbor in image classification algorithm by proposing efficient method for similarity measure. Generally in supervised classification, after finding the feature vectors of training images and testing images, nearest neighbor classifier does the classification job. This classifier uses different distance measures such as Euclidean distance, Manhattan distance etc. to find the nearest training feature vector. This paper proposes to use Mean Squared Error (MSE) to find the nearness between two images. Initially Independent Principal Component Analysis (PCA),which we discussed in our earlier work, is applied to images of each class to generate Eigen coordinate system for that class. Then for the given test image, a set of feature vectors is generated. New images are reconstructed using each Eigen coordinate system and the corresponding test feature vector. Lowest MSE between the given test image and new reconstructed image indicates the corresponding class for that image. The experiments are conducted on COIL-100 database. The performance is also compared withÂ distance based nearest neighbor classifier. Results show that the proposed method achieves high accuracy even for small size of training set.